Comparison of strength and durability properties between earth‑cement blocks and cement–sand blocks - Yogananth, Y.; Thanushan, K.; Sangeeth, P.; Coonghe, J.G.; Sathiparan, N. (Springer, 2019)
In recent years, due to the growth of the construction industry in Sri Lanka, the consumption of river sand has increased. Because of overexploitation of river sand and its various harmful environmental and social consequences, sand mining is limited by authorities, and therefore, there is a scarcity for good quality river sand at a reasonable cost. As a result, local soil is used for the production of masonry units as sand replacement material. In this study, to compare the performance of cement–sand blocks (CSBs) and earth-cement blocks (ECBs), three different cement:sand and cement:local soil mix ratios were considered for CSBs and ECBs, respectively. An experimental program was carried out to determine the physical, strength and durability characteristics of both block types. The results show that ECBs performed better in dry compressive strength and most of the durability characteristics. However, strength reduction due to wet conditions is a major issue for ECBs.
Keywords: Earth-cement blocks; cement–sand blocks